SIREP Sebagai Immunomodulator pada Lansia dengan Gangguan Pemenuhan Tidur - Joni Haryanto; Suhartono Taat Putra (Jurnal Ners, 2007)
Introduction: Sirep is one of the nursing intervention to solve sleep problems. Moreover, sirep as immunomodulator for cortisol level, IFN-γRa and IL-10 is still unknown.       Sleep disorder can make decrease of immunity, concentration disability, decrease of coordination, alteration of personality, etc. Decrease of immunity can caused by increase or imbalance of stress hormone (cortisol). Increase of cortisol in along time can suppresed T lymphocytes. Objective of this study was to analyze the effect of sleep therapy (sirep) as immunomodulator in elderly with sleep disorder Method: This study used Quasy-Experimental Pre-Post Test Control Group Non Randomised design. Result: Result showed that Sleep therapy (sirep) can changed IFNgRa level in serum elderly with Wilcoxon Sign Rank Test had p<0.01 and Mann Whitney U-Test had  p<0.01. Sleep therapy (sirep) can be change IL-10 level serum of elderly could be concluded that there was significant difference with Wilcoxon Sign Rank Test had p<0.01 and Mann Whitney U-Test not significant difference had  p>0.01. Discussion: Sleep therapy of elderly can released cortisol level serum changing, so sleep therapy as immunomodulator in elderly with sleep dissorder was verified. Discussion: Sleep therapy must applied on elderly with sleep disorder, because sleep therapy become immunomodulator on elderly with sleep disorder was verified.